Effect of asset quality, rentability, and liquidity on the book value of bank companies listed on the idx in 2015-2020 - Effendi Tjahjadi; Riris Rotua Sitorus (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
PBV is an important spotlight for investors to find out the book value of a company which can provide an overview of the value of shares per share. The purpose of this study is to measure how strong the impact of asset quality, profitability, and liquidity is on a company's book value. This research is conducted quantitatively and utilizes secondary data from the bank's annual report. The sample data that met the requirements to be processed were 23 banks for a period of 6 years to become 138 sample data. The results of the data test show that NPL, ROE, ROA, OER, and LDR together have a positive significant impact on the Book Value of Shares, individually NPL has a significant positive impact, ROE has a significant positive impact, ROA has a positive and significant impact, OER has no impact and liquidity has a significant positive impact on the Book Value of Shares. Asset quality, profitability and liquidity scores are indicators of financial performance that can be used by fund owners to determine the condition of a bank's financial health when investing in banking stocks based on the right decisions. Every banking organization should improve its financial performance to achieve Bank Indonesia-regulated bank soundness.